1994
DOI: 10.1002/fld.1650191102
|View full text |Cite
|
Sign up to set email alerts
|

Numerical predictions of the bifurcation of confined swirling flows

Abstract: The bifurcation of confined swirling flows was numerically investigated by employing both the k--E and algebraic stress turbulence models. Depending upon the branch solution examined, dual flow patterns were predicted at certain swirl levels. In the lower-branch solution which is obtained by gradually increasing the swirl level from a low-swirl flow, the flow changes with increasing swirl number from the low-swirl flow pattern to a high-swirl flow pattern. In the upper-branch solution which is acquired by grad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…The results showed that the standard and the Durbin k-ε models gave the best agreement with the experimental data. This supported the finding of Jiang and Shen (1994) and Durst and Wennerberg (1991) where good agreement between k-ε model predictions and experimental result were reported.…”
Section: Turbulence Modelingsupporting
confidence: 91%
“…The results showed that the standard and the Durbin k-ε models gave the best agreement with the experimental data. This supported the finding of Jiang and Shen (1994) and Durst and Wennerberg (1991) where good agreement between k-ε model predictions and experimental result were reported.…”
Section: Turbulence Modelingsupporting
confidence: 91%
“…The reverse flow was much more pronounced in the RNG k-ε model, which penetrated almost the entire extension of the annular duct, reaching an axial velocity of -4 m/s at the annular duct exit and a peak of approximately 22 m/s, in comparison with 19 m/s for the k-ε model. The reverse flow in the annular region was practically imperceptible with the standard k-ε model, and, despite the observations of Jiang and Shen (1994) for rotating flow in a tube expansion, each turbulence model showed distinct results. However, the effects of using the results obtained for the upwind scheme as a necessary initial condition to obtain convergence in the higher-order upwind scheme requires a more extensive investigation.…”
Section: Resultsmentioning
confidence: 73%
“…Conversely, the lack of agreement between the experimental data and the predictions regarding swirling flows could be attributed, as mentioned by Jiang and Shen (1994), to the phenomenon of bifurcation, in which one given swirl number can be associated with two distinct conditions of steady state flow. This phenomenon of non-unique steadystate behavior occurs as a consequence of the existence of two paths through which the desired swirl number can be obtained, that is by the gradual increase in the intensity of the swirl, the lower branch, or, alternatively, by the gradual reduction in the intensity of the swirl from a higher condition, the upper branch, such that the predicted swirl number can differ significantly from the experimental swirl number depending on the path.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations